From Suffix To Prefix To Interposition Via Differential Object Marking In Egyptian-Coptic - Grossman, Eitan (My University, 2018)
This article argues that Differential Argument Indexing (DOI) and Differential Argument Marking (DOM) constructions in Coptic (Afroasiatic, Egypt) are reanalyzed, resulting in a set of verbs with interposed P-indexes within bipartite stems (DeLancey 1996; Nichols 2003). Basically, incorporated noun phrases with prefixed possessor indexes become parts of derived verbs with unpredictable lexical semantics, and their erstwhile possessor prefixes, entrapped within the derived verb, are reanalyzed as P-interpositions. Since this possessor prefix ultimately developed from an earlier possessor suffix, the pathway documented here, stripped down to its essentials, is suffix → prefix → interposition, and erstwhile complex construction → bipartite stem. Finally, an overt genitive prefix that marks lexical possessors of incorporated noun phrases is reanalyzed as an accusative case prefix. These changes introduce new complexity into Coptic Differential Argument Marking: not only are P arguments either indexed as suffixes, case marked, or incorporated for the majority of verbs, they can be indexed as interpositions for a lexically determined set of verbs.
Keywords: Coptic; affix ordering; noun incorporation